2016
DOI: 10.1038/srep38930
|View full text |Cite
|
Sign up to set email alerts
|

Urinary KIM-1: a novel biomarker for evaluation of occupational exposure to lead

Abstract: Chronic occult lead poisoning often develops ensuing occupational lead exposure. Early diagnosis of lead poisoning is critical for timely discontinuation of lead exposure and for prognosis. This study explored the value of urinary kidney injury molecule-1 (KIM-1) in diagnosing renal injury induced by lead at an early stage. We retrospectively analyzed 92 workers exposed to occupational lead and demonstrated a better correlation ship between blood lead levels and urine excretion of KIM-1 than other traditional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 35 publications
(41 reference statements)
0
15
1
Order By: Relevance
“…In our study, there was no significant difference between the mean UAs concentrations between the three groups, but the levels were higher than the US population data indicating possible exposure. Both seafood and rice can contribute to elevated UAs levels [27][28][29][30]. In the present study, we did not gather information about the sea fish intake of the participants.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In our study, there was no significant difference between the mean UAs concentrations between the three groups, but the levels were higher than the US population data indicating possible exposure. Both seafood and rice can contribute to elevated UAs levels [27][28][29][30]. In the present study, we did not gather information about the sea fish intake of the participants.…”
Section: Discussionmentioning
confidence: 85%
“…Rice cultivators can accumulate both inorganic and organic forms of arsenic. The proportion of inorganic arsenic in rice grain differs according to the variety [29,30]. Urinary Pb levels were significantly higher in farmer controls than CKDu patients and non-farmer controls.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, a cross-sectional study of Korean adults demonstrated a positive correlation between blood Pb levels and renal dysfunction [ 270 ]. Additionally, erythrocyte Pb appears to be associated with renal injury [ 271 ].…”
Section: Environmentally Relevant Toxic Metalsmentioning
confidence: 99%
“…For instance, high level of copper in water environment particularly in drinking water may cause Wilson's disease, which leads to accumulation of copper in tissues such as the liver and brain, thus leading to liver disease as well as psychiatric and neurological symptoms to human (Stock, Reuner, Gohll, & Beste, 2016). In addition, it has been reported that lead exposure was accounted for about 853,000 deaths in 2013 due to long-term effects on health, with the highest number of cases in low and middle-income countries (Zhou et al, 2016). Many industrial processes involve heavy metals as important components for electrical appliances.…”
Section: Introductionmentioning
confidence: 99%